(untitled) (Costos y Gestión, 2020)
The study aimed to identify the costs and establish the formation of the price of sale of products in a bakery industry located in the western region of the State of Santa Catarina. The instruments used for the data collection were: unstructured interview, documentary analysis and direct observation. Data analysis was performed quantitatively by presenting data related to activity costs. The results indicated that in the bakery industry, homemade bread and plain cakes generate high profitability, where homemade bread showed a 31% profit margin and a simple profit margin of 17%. In addition, it is concluded that the absorption cost method indicated that homemade bread is more profitable than plain bread.